IDENTITAS TIONGHOA-INDONESIA MELALUI HERMENEUTIKA TIPOLOGI BONGPAY DI BONG MUNTANG-TANJUNG BANYUMAS - Tri Asiati Sutito (Asosiasi Program Studi Mandarin Indonesia, 2017)
Chinese-Indonesian term implies Chinese position and contribution to Indonesian cultural dynamic. This term refers to their adaptation in Indonesia as homeland instead of migrating destination. Nevertheless, they keep on taking care and preserving the bond with the Chinese by expression and the existence of tribute devoted to the ancestors which showed as Bongpay. In this significance, Bongpay is not merely sadness marker of a farewell, but the expression of Chinese conception to honor theirs ancestors with various typologies. In this ways, using hermeneutic method as a data interpretation to totality explain about theirs particular identity as a part of Indonesian society based on typology of Bongpay likely cultural artifact, Chinese existence, and society response.